2017
DOI: 10.5194/bg-14-3111-2017
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying nutrient uptake as driver of rock weathering in forest ecosystems by magnesium stable isotopes

Abstract: Abstract. Plants and soil microbiota play an active role in rock weathering and potentially couple weathering at depth with erosion at the soil surface. The nature of this coupling is still unresolved because we lacked means to quantify the passage of chemical elements from rock through higher plants. In a temperate forested landscape characterised by relatively fast ( ∼ 220 t km −2 yr −1 ) denudation and a kinetically limited weathering regime of the Southern Sierra Critical Zone Observatory (SSCZO), Californ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(104 citation statements)
references
References 66 publications
2
102
0
Order By: Relevance
“…Their findings imply that plant roots facilitate rock weathering and production of ‘fracture fill’ (i.e. loose, soil‐like material in fractures) at depth, and lend support to the findings of Uhlig et al () that plant roots also take up nutrients from fracture environments (Fig. ).…”
Section: Elements Sourced From Weathered Bedrock and Dust Determine Esupporting
confidence: 79%
See 1 more Smart Citation
“…Their findings imply that plant roots facilitate rock weathering and production of ‘fracture fill’ (i.e. loose, soil‐like material in fractures) at depth, and lend support to the findings of Uhlig et al () that plant roots also take up nutrients from fracture environments (Fig. ).…”
Section: Elements Sourced From Weathered Bedrock and Dust Determine Esupporting
confidence: 79%
“…Alongside a focus on nutrient inputs to terrestrial ecosystems, CZ research is beginning to reveal deep subsurface elemental cycling driven by plants, within bedrock fractures. Through an innovative application of Mg stable isotopes and elemental mass balance, Uhlig et al () demonstrated that nutrients (P, K, Mg, Ca and Si) are directly incorporated into plant biomass from weathering of parent material within the rock moisture zone, providing evidence of plant acquisition of nutrients at depth. Taking a different approach, Hasenmueller et al () described the physical and biogeochemical environment of tree roots extending from surface soils into fractured bedrock using a series of pits to assess plant–rock interactions and the potential of plant‐mediated weathering of rock to regolith.…”
Section: Elements Sourced From Weathered Bedrock and Dust Determine Ementioning
confidence: 99%
“…Procedures for Mg purification and isotope ratio measurements are similar to those described previously (Uhlig et al . ). A brief description of the method applied during this study is given below.…”
Section: Methodsmentioning
confidence: 97%
“…The basic idea of the cycling module, described more fully in section , was to account for the well‐known phenomenon of biolifting and nutrient cycling of base cations and Si through vegetation. Specifically, Ca, K, Mg, and Si cycle through vegetation approximately 10–40 times before exiting soils and entering rivers (Uhlig et al, ). The cycling of soluble nutrient cations is expected to increase concentrations in the upper soil layers to a much greater extent than could be achieved through the chemical weathering of clay minerals alone in those upper layers.…”
Section: Modeling Resultsmentioning
confidence: 99%